Simultaneously Enhancing the Dynamic Damping and Static Strength Capabilities of Structures: A Case Study Conducted on Fly Ash-based Geopolymer Concrete Specimens using Modal, Mechanical and Microstructural Investigations - Çeçen, Ferhat; Özbayrak, Ahmet; Aktaş, Bekir (Fırat University, 2024)
Enhancing both the dynamic damping and static strength of ordinary Portland cement (OPC) concrete simultaneously is a significant challenge. Geopolymer concrete (GPC), particularly fly ash-based GPC, offers a promising alternative. This study explores the relationship between damping and strength in heat-cured, low-calcium fly ash-based GPC using sodium silicate (SS) and sodium hydroxide (SH) activators. The findings reveal that SS activators demonstrate stronger positive correlations between damping and strength compared to SH activators. Microstructural analysis indicated that increasing SS dosage from 55 kg/m³ to 98 kg/m³ resulted in a 17% increase in dynamic damping ratios and a 39% increase in static compressive strength. These results highlight the potential of GPC to surpass OPC concrete in applications requiring both enhanced damping and strength, offering a dual benefit not typically achievable with OPC. The study contributes to a deeper understanding of GPC's capabilities, paving the way for its broader adoption in construction projects.

Portland çimentosu (OPC) betonu için hem dinamik sönümlemeyi hem de statik dayanımı aynı anda artırmak, önemli bir zorluktur. Geopolimer beton (GPC), özellikle uçucu kül bazlı GPC, umut verici bir alternatif sunmaktadır. Bu çalışma, düşük kalsiyumlu uçucu kül bazlı GPC'de sönümleme ve dayanım arasındaki ilişkiyi, sodyum silikat (SS) ve sodyum hidroksit (SH) aktivatörleri kullanarak araştırmaktadır. Bulgular, SS aktivatörlerinin SH aktivatörlerine kıyasla sönümleme ve dayanım arasında daha güçlü pozitif korelasyonlar gösterdiğini ortaya koymaktadır. Mikroyapı analizi, SS dozajının 55 kg/m³'ten 98 kg/m³'e artırılmasının dinamik sönümleme oranlarında %17 ve statik basınç dayanımında %39 artışa neden olduğunu göstermiştir. Bu sonuçlar, GPC'nin OPC betona kıyasla her iki özelliğin de artırılması gereken uygulamalarda üstün olma potansiyelini vurgulamakta ve OPC ile tipik olarak elde edilemeyen çift fayda sunmaktadır. Çalışma, GPC'nin yeteneklerini daha iyi anlamaya katkıda bulunarak, inşaat projelerinde daha geniş çapta benimsenmesinin önünü açmaktadır.
Yapıların Dinamik Sönümleme ve Statik Dayanım Yeteneklerinin Eş Zamanlı Olarak Geliştirilmesi: Uçucu Kül Esaslı Geopolimer Beton Numuneler Üzerinde Modal, Mekanik ve Mikroyapısal İncelemeler Kullanılarak Gerçekleştirilen Bir Vaka Çalışması
Keywords: Reinforced Concrete Buildings; Betonarme Yapılar; Earthquake Engineering; Deprem Mühendisliği